A dendrite-free and anticaustic Zn anode enabled by high current-induced reconstruction of the electrical double layer - Cui, Yang-feng; Cao, Ren-fei; Du, Jia-yi; Zhuang, Zhen-bang; Xie, Zi-long; Wang, Qing-shuang; Bao, Di; Liu, Wan-qiang; Zhu, Yun-hai; Huang, Gang (Chemical communications (Cambridge, England), 2023)
Aqueous Zn-based batteries deliver thousands of cycles at high rates but poor recyclability at low rates. Herein, we reveal that this illogical phenomenon is attributed to the reconstructed electrode/electrolyte interface at high rates, wherein the condensed electrical double layer (EDL) and the tightly absorbed Zn 2+ ions on the Zn electrode surface afford compact and corrosion-resistant Zn deposits. The densely textured and corrosion-resistant Zn anode was achieved by reconstructing the EDL structure via high current density, enabling durable battery performance.